Ruthenium-Mediated 18F-Fluorination and Preclinical Evaluation of a New CB1 Receptor Imaging Agent [18F]FPATPP - Lahdenpohja S; Rajala N; Helin JS; Haaparanta-Solin M; Solin O; López-Picón FR; Kirjavainen A (ACS Publisher, 2022)
Cannabinoid receptor 1 (CB1R) controls various physiological and pathological conditions, including memory, motivation, and inflammation, and is thus an interesting target for positron emission tomography (PET). Herein, we report a ruthenium-mediated radiolabeling synthesis and preclinical evaluation of a new CB1R specific radiotracer, [18F]FPATPP. [18F]FPATPP was produced with 16.7 ± 5.7% decay-corrected radiochemical yield and >95 GBq/μmol molar activity. The tracer showed high stability, low defluorination, and high specific binding to CB1Rs in mouse brain.